Lead, Sulfur, and Oxygen Isotope Systematics in Hydrothermal Precipitates from the 14°S Hydrothermal Field, South Mid‐Atlantic Ridge. Issue 3 (July 2016) - Li, Bing; Shi, Xuefa; Li, Chuanshun; Wang, Jixin; Pei, Yanliang; Ye, Jun
Abstract: At the inside corner between the South Mid‐Atlantic Ridge (SMAR) and the Cardno fracture zone, the 14°S hydrothermal field, with its abundant silica‐rich sulfides, was identified as a volcanic massif, which provided the first opportunity to study inside corner‐related hydrothermal mineralization. S, Pb, and O isotopes were measured in hydrothermal sulfide samples from the two sites (volcanic top and slope sites) in the 14°S field. The homogeneous Pb isotope values ( 207 Pb/ 204 Pb = 15.466 − 15.472; 206 Pb/ 204 Pb = 18.242 − 18.252) and the δ 34 S values (top site, +6.3 to +6.85‰; slope site, +2.37 to +3.36‰) suggest that the source of metals and most of the sulfur is the upper crust, whereas some sulfur is sourced from downward‐penetrating seawater, especially in the top site. The calculated oxygen isotope equilibration temperatures from quartz and seawater are between 94 and 144°C for the top site and between 179 and 196°C for the slope site. These isotopic proxies, together with geological background survey data, have an important implication: Discrepancies between the sites may result from variations in crust permeability, which also affect the mixing level between downward‐penetrating seawater and upward hydrothermal end‐member fluids and determine the various mineralization types. Abstract : Pb isotope of silica‐rich sulfides suggest that fluid in two discharge sites of 14°S hydrothermal field is supplied by a single large hydrothermal system. The difference in S and O isotope of silica‐rich sulfides are considered to be due to the differences in the fluid path length in the inside corner volcanic massif, and crustal permeability which affect the mixing level between downward‐penetrating seawater and upward hydrothermal end‐member fluids.